Dual solutions of magnetohydrodynamic stagnation point flow and heat transfer of viscoelastic nanofluid over a permeable stretching/shrinking sheet with thermal radiation - Rahimah, Jusoh; Roslinda, Nazar; Pop, I. (IOP Publishing, 2017)
The present study is intended to encompass the stagnation point flow and heat transfer of viscoelastic nanofluid with the presence of thermal radiation. The viscous incompressible electrically conducting and Jeffrey fluid model is taken into account. The governing partial differential equations are reduced to ordinary differential equations by using the appropriate similarity variables. The resulting differential equations are solved numerically using the built in bvp4c function in Matlab. Dual solutions are discovered for a certain range of the governing parameters. Numerical results for the velocity and temperature profiles as well as the skin friction coefficients and the local Nusselt number are elucidated through tables and graphs.